L’efficacité de la formation à distance au niveau postsecondaire : une méga-analyse - Simard, Yanik; Gauthier, Clermont; Richard, Mario (Canadian Journal of Higher Education, 2019)
In Canada, distance education (DE) is present in the majority of post-secondary institutions. However, there is a constant polemic in the scientific community. This is the controversial impact of technological advances on the effectiveness of this type of training. Some authors highlight the positive contribution of these advances while others emphasize the many disappointments caused by the use of newer technologies. In the face of these conflicting positions, several researchers agree that studies on the effectiveness of DE based on technological advances are still in their infancy. To fill this gap, the objective of this research is to verify the effectiveness of the DE based on technological advances using a mega-analysis. Based on a synthesis of 16 meta-analyses involving 862 primary studies involving over 200,000 participants, the positive results obtained by our mega-analysis would support the use of more recent technologies to promote distance learning.